TOUCHSTONE, WIREPULLER AND TRANSITION: SINO-KOREAN BOOK-DIPLOMACY AND POLITICAL FIGHTS IN 1597-1599 - HUANG, Xiu Zhi (International Journal of Korean Humanities and Social Sciences, 2017)
Embodying an optimistic diplomatic mind in early Joseon Dynasty, haidongzhuguoji written by Shin Suk-ju became a main evidence of Chinese official Ding Yingtai impeaching Joseon in the Jeongyu War occurring in 1597 because of Toyotomi Hideyoshi’s second invasion. Ding Yingtai’s impeachment involved Joseon’s king, Chinese generals in Joseon and officials in Beijing in a political maelstrom, which aroused strong reactions of Joseon king and ministers. In this situation, Joseon’s diplomatic corps were dispatched to Beijing in order to justify and defend. They made preparations and took action zealously, winning the final victory and achieving the goal consequently. However, this book-diplomacy surpassed the problem of justifying a book, thus there were some complicated and subtle meanings in the process. Firstly, This book-diplomacy provided a touchstone of Sino-Korean relationship in Ming Dynasty, explaining the political essence of the relationship. Secondly, This diplomacy resulted from Ming Dynasty’s political fights and calmed down also because of Ming Dynasty’s political fights, intensively showing both Sino-Korean interdependent political fights and each liege fights. Thirdly, The book-diplomacy became an important turning point of the transformation of Joseon’s foreign concept, and Joseon’s “Smaller China” mind began to emphasize excluding barbarians, which made an idealistic preparation for the rising “Smaller China” mind in Qing Dynasty.